2016
DOI: 10.1590/1518-8345.0363.2703
|View full text |Cite
|
Sign up to set email alerts
|

Educational intervention for collecting sputum for tuberculosis: a quasi-experimental study

Abstract: Objective: to evaluate the quality of the sputum sample before and after the Nursing guidance to patients. Methods: this is a quasi-experimental research design, single group type, before and after, non-randomized study. The study enrolled patients with suspected pulmonary tuberculosis, respiratory symptomatic patients for over three weeks, aged over 18 years, of both genders and without tuberculosis history in the last two years. The educational intervention consisted of individualized guidance on the collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 13 publications
0
16
0
15
Order By: Relevance
“…In some previous reports, improving sputum quality increased TB diagnostic yield [18, 20-24]. Ho et al were able to collect 99% mucoid or muco-purulent sputa by using sputum quality colour scale [18,20]; Alisjahbana et al , used instruction to patients, where patients were individually addressed on the importance of sputum examination and how to produce adequate samples; this technique demonstrated an improvement in sputum volume collection with thicker consistency and resulting in higher smear positivity rates [21]; Sicsu et al and Hirooka et al using similar methods as Alisjahbana et al showed higher quality and volume sputum samples that resulted in increased bacteriologically-confirmed TB diagnosis [22, 23]. Mhalu et al demonstrated that sputum submission instructional videos increased the yield of TB cases through better quality of sputum samples [24].…”
Section: Discussionmentioning
confidence: 99%
“…In some previous reports, improving sputum quality increased TB diagnostic yield [18, 20-24]. Ho et al were able to collect 99% mucoid or muco-purulent sputa by using sputum quality colour scale [18,20]; Alisjahbana et al , used instruction to patients, where patients were individually addressed on the importance of sputum examination and how to produce adequate samples; this technique demonstrated an improvement in sputum volume collection with thicker consistency and resulting in higher smear positivity rates [21]; Sicsu et al and Hirooka et al using similar methods as Alisjahbana et al showed higher quality and volume sputum samples that resulted in increased bacteriologically-confirmed TB diagnosis [22, 23]. Mhalu et al demonstrated that sputum submission instructional videos increased the yield of TB cases through better quality of sputum samples [24].…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, identificou-se um número significativo de pacientes não realizaram a primeira e segunda baciloscopia de escarro. Considerando que esse é um exame de baixo custo, fácil acesso e com níveis consideráveis de assertividade para o diagnóstico da doença, seria importante que as equipes de saúde envolvidas no atendimento ao paciente portador ou suspeito de TB se atentassem para a realização desse exame a fim de melhorar esses índices 24,25 . A cultura de escarro é considerada por alguns profissionais como um exame mais complexo, de maior custo e com maior tempo de realização.…”
Section: Discussionunclassified
“…Contudo, identificou-se um número significativo de pacientes não realizaram a primeira e segunda baciloscopia de escarro. Considerando que esse é um exame de baixo custo, fácil acesso e com níveis consideráveis de assertividade para o diagnóstico da doença, seria importante que as equipes de saúde envolvidas no atendimento ao paciente portador ou suspeito de TB se atentassem para a realização desse exame a fim de melhorar esses índices 24,25 .…”
Section: Discussionunclassified